2021
DOI: 10.3390/children8020070
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Virtual Reality-Based Interventions for Children and Adolescents with ADHD: A Systematic Review and Meta-Analysis

Abstract: This review aims to evaluate the effectiveness of virtual reality-based interventions (VR-based interventions) on cognitive deficits in children with attention deficit hyperactivity disorder (ADHD). A systematic review and meta-analysis were performed according to the PRISMA statement and the Cochrane Handbook guidelines for conducting meta-analyses. The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) was used to assess the quality of the evidence. Clinical trials published up to 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…NF improved the symptomatology in children with ADHD, because of learning through video games, attending to their mistakes, and training functions nonconscious control-such as attention, achievement of objectives, self-control, and self-regulation of attention levels, and concentration-in addition to inhibiting distracting stimuli [35]. Also, it was found evidence of comparative effectiveness of NF and CogT for children with ADHD.…”
Section: Discussionmentioning
confidence: 90%
“…NF improved the symptomatology in children with ADHD, because of learning through video games, attending to their mistakes, and training functions nonconscious control-such as attention, achievement of objectives, self-control, and self-regulation of attention levels, and concentration-in addition to inhibiting distracting stimuli [35]. Also, it was found evidence of comparative effectiveness of NF and CogT for children with ADHD.…”
Section: Discussionmentioning
confidence: 90%
“…Researchers used VR and artificial Intelligence (AI) where participants are presented with multiple VR scenes in which visual, auditory and vestibular senses are stimulated and input to an AI model, which classifies these behaviours. A review by Romero-Ayuso et al. (2021) concluded that VR interventions in children and adolescents with ADHD show mixed results, where sustained attention and attentional vigilance are improved; however, impulsivity responses showed no changes.…”
Section: Virtual Reality (Vr) and Autism/adhdmentioning
confidence: 99%
“…Despite emerging promising work on VR use to understand ADHD (Hong et al. , 2021; Romero-Ayuso et al. , 2021; Son et al.…”
Section: Virtual Reality (Vr) and Autism/adhdmentioning
confidence: 99%
“…Likewise, the study of Riquelme, Sabater-Gárriz and Montoya [ 11 ] delves into the impact on the family of chronic pain in children with cerebral palsy (CP) and its relationship to the quality of life of these children and their ability to communicate. This volume also addresses the effectiveness of two types of emerging therapies: hypnotherapy in children with CP [ 12 ] and the use of virtual reality in children with attention-deficit hyperactivity disorder (ADHD) [ 13 ]. Both studies allow us to advance the available evidence.…”
mentioning
confidence: 99%
“…Thus, it is concluded that hypnotherapy, for 8–12 weeks, stimulates proprioceptive and balance reactions, reducing muscle spasticity, through rhythmic and symmetrical movement, leading to an improvement in the gross motor function in children with CP, such as lying down, roll, sitting and walking [ 12 ]. The meta-analysis of Virtual Reality-Based Interventions for Children and Adolescents with ADHD highlights the need to design randomized controlled trials with virtual reality and concludes that virtual reality may be effective in improving performance in sustained attention tasks in children with ADHD [ 13 ].…”
mentioning
confidence: 99%